Solid fuels and heavy hydrocarbon liquids : thermal characterization and analysis - Kandiyoti, R. (Rafael) (Elsevier, 2006)
The first strand involves a critical overview of the design of experimental methods used for examining the thermal behaviour of solid fuels [pyrolysis, liquefaction and gasification], while the second will emphasise chemical structures and molecular mass distributions of coal derived tars, extracts and pitches, petroleum-derived asphaltenes, and biomass derived heavy hydrocarbon liquids. Two major, interdependent strands in the study of fossil and renewable fuel utilisation are focused on within this text: (i) Thermal characterisation of solid fuels including various ranks of coals, biomass and waste, and, (ii) The analytical characterisation of heavy hydrocarbon liquids, covering coal, petroleum and biomass derived heavy fractions. Two major, interdependent strands in the study of fossil and renewable fuel utilisation are focused on within this text: (i) Thermal characterisation of solid fuels including various ranks of coals, biomass and waste, and, (ii) The analytical characterisation of heavy hydrocarbon liquids, covering coal, petroleum and biomass derived heavy fractions.